A Miniaturize Bandpass Filter with Harmonic Suppression Using Meandered Quarter-Wavelength Resonators. (18th February 2014) - Lu, Yun-Long; Wang, Shun; Gu, Tingting; Cao, Ping; Li, Kai
Abstract : A miniaturized bandpass filter with harmonics suppression is presented. The proposed filter consists of two quarter-wavelength microstrip resonators, which are meandered for circuit size reduction. An interdigital capacitor, loading at zero-voltage point, is employed to provide the desired coupling between the resonators at operating frequency, whereas the coupling coefficient at the third harmonic is realized to be zero. Besides, the second and fourth harmonics are suppressed since λ /4 resonators are adopted. Benefiting from these properties, a miniaturized bandpass filter with the second, third, and fourth harmonics suppression was designed and implemented. The final measured and simulated results show good consistence with the theoretical counterparts.